Production of coal briquettes using the original binder - Mustafin, E.S.; Omarov, Kh.B.; Shaimerdenova, K.M.; Omerkulov, A.T. (KSU publ., 2019)
In this paper the authors consider a new genuine binder that makes it possible to produce coal briquets with desired consumer properties, i.e. reduced bitumen consumption, low production process temperatures and high moisture resistance. To make coal briquets, a batch mixture was prepared (coal fines, slack, riddlings) and then mixed in a mixer with a genuine emulsified bitum in a ratio of 20 to 1 by weight, after which the mixture was fed into molds and taken to a pressing machine. The resulting briquets were dried at a temperature of 30–40 ºC for 12 hours. The results of their tests displayed a compressiion strength of 60–70 kg/cm2; when dropped from a height of one meter, the residue on the sieve +25 mm after sieving was 96–98 % (high strength). In addition, the briquets showed good resistance to moisture (low moisture capacity not more than 2–3 %) — water sprinkling did not loose the briquettes; there was no destruction even when doused into water. In the process of burning the briquets did not disintegrate, the flame was uniform in all directions. Calorific capacity tests of the produced briquets were made. Due to the improved commercial quality offered by briquees, after scoping calculations the saving of coal fuel was presupposed.
Keywords: coal briquettes; coal fines; mixture; slack; bitumen; moisture resistance; binder; calorific capacity